2016
DOI: 10.1002/tcr.201600021
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Nazarov Cyclizations: The Use of Iron Salts as Catalysts in Ionic Liquid Solvent Systems

Abstract: Nazarov cyclization is an important and versatile method for the synthesis of five-membered carbocycles, and extensive studies have been conducted to optimize the reaction. Among recent studies, several trends are recognized. One is the combination of different reactions with Nazarov cyclization in a one-pot reaction system which enables the preparation of unique cyclization products. The second is the use of a transition-metal catalyst, though Lewis or Brønsted acids have generally been used for the reaction.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 86 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…We have explored MOF‐based catalysts for tandem acylation–Nazarov cyclization reactions . The reaction is an acid‐catalyzed acylation followed by 4π‐electrocyclic process to build a new carbon–carbon bond for the synthesis of cyclopentenone, which is the key intermediate in the synthesis of numerous biologically active molecules and highly functional compounds . Recently, on the basis of the high catalytic activity, robustness, and excellent selectivity of MOF‐based catalysts, we have reported highly efficient Zn‐MOF and Ag‐MOF for the synthesis of cyclopenta[ b ]pyrroles by treatment of pyrrole derivatives with α,β‐unsaturated carboxylic acids .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have explored MOF‐based catalysts for tandem acylation–Nazarov cyclization reactions . The reaction is an acid‐catalyzed acylation followed by 4π‐electrocyclic process to build a new carbon–carbon bond for the synthesis of cyclopentenone, which is the key intermediate in the synthesis of numerous biologically active molecules and highly functional compounds . Recently, on the basis of the high catalytic activity, robustness, and excellent selectivity of MOF‐based catalysts, we have reported highly efficient Zn‐MOF and Ag‐MOF for the synthesis of cyclopenta[ b ]pyrroles by treatment of pyrrole derivatives with α,β‐unsaturated carboxylic acids .…”
Section: Introductionmentioning
confidence: 99%
“…[17] The reaction is an acidcatalyzed acylation followedb y4 p-electrocyclicp rocess to build an ew carbon-carbon bond for the synthesis of cyclopentenone, which is the key intermediate in the synthesis of numerousb iologically active molecules and highly functional compounds. [18][19][20] Recently,onthe basis of the high catalytic ac-tivity,r obustness, and excellent selectivity of MOF-based catalysts, we have reported highly efficient Zn-MOFa nd Ag-MOF for the synthesis of cyclopenta[b]pyrroles by treatment of pyrrole derivatives with a,b-unsaturated carboxylic acids. [21] Recently,w eaimed to develop an MOF-catalyzed tandem acylation-Nazarov cyclization reaction of benzene and a,b-unsaturated carboxylic acid for the formationo fc yclopentenone[b]benzene, which is the skeleton of af amily of natural products with significantly antitumora ctivitiesa nd aromatase inhibitory activities( taiwaniaquinones).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors, such as the use of concentrated protic acids as catalyst, high reaction temperatures and generally poor regioselectivity, have limited the synthetic utility of this reaction, which has long been studied mainly from a mechanistic point of view . The utilization of Lewis acids as catalysts, the use of aprotic media, and various innovations and optimizations have greatly extended the scope of application of this reaction in organic synthesis . One of these breakthroughs in the development of the Nazarov cyclization was the interrupted reaction, which differs from the classical version by the formation of, as a rule, substituted cyclopentanones 5 , due to the reaction of the oxyallyl carbocation 4 with various nucleophiles (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, our laboratory has paid close attention to develop MOF-based heterogeneous catalysts to execute tandem acylation–Nazarov cyclization reactions. It belongs to a class of acid-catalyzed acylation, followed by 4π-electrocyclization to construct five-membered carbocycles for synthesizing of cyclopentenone frameworks, which are important intermediates in preparing numerous natural products, such as roseophilin, bruceolline E, taiwaniaquinol, and so on. We recently showed that the Zn-MOF and Ag-MOF had displayed to be valable solid catalysts to facilitate cascade pyrrole dervatives cyclization reactions for producing cyclo­penta­[ b ]­pyrrole skeletons. , Inspired by preliminary results, we would like to explore MOFs-based catalysts for cascade indole derivatives cyclization reactions for producing cyclo­pen­tenone­[ b ]­indoles skeletons. However, employing a series of Brønsted acids (such as TFA, HCl, or H 3 PO 4 ), Lewis acids (such as BBr 3 , anhydrous AlCl 3 , SnCl 4 , anhydrous FeCl 3 , or ZnCl 2 ), or MOFs (Ag-MOFs and Zn-MOFs) as homogeneous or heterogeneous catalysts usually produced no products or the acylation products with a modicum of the cyclization products since indole had the lesser electron cloud density compared with that of pyrrole. Therefore, immobilizing of the high density of Lewis acidic active sites with continuous and ordered membranes utilizing a solid support to construct stable MOF-based membranes to simulate the complex characteristics of natural classification for tandem reactions can provide an interesting approach to afford the benefit of readily accessible active sites with minimum diffusion distance for the cascade indole cyclization reaction for producing cyclo­pent­enone­[ b ]­indoles skeletons.…”
Section: Introductionmentioning
confidence: 99%